2010
DOI: 10.1111/j.1440-1746.2009.06038.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrogastrographic characteristics in subjects with stomach remnant

Abstract: Distal RSG patients may have decreased SW frequency and less meal ingestion changed EGG parameters in terms of SW frequency, normality and stability, whereas their EGG power remained unchanged irrespective of meal ingestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…However, it did reveal significant temporal differences in the percentage of bradygastria for postprandial recordings between 1 week and 3 months and between 1 week and 6 months but not between 3 months and 6 months. Unlike other studies that obtained a DF of ~3 cpm in the gastric remnant, Lee et al18 found that distal RSG patients had a lower DF value with an increased percentage of bradygastria (<2 cpm) irrespective of meal ingestion. Bracci et al28 observed the less common 3 cpm with an increased chance of bradygastria in children who underwent partial gastrectomy to augment bladder function.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, it did reveal significant temporal differences in the percentage of bradygastria for postprandial recordings between 1 week and 3 months and between 1 week and 6 months but not between 3 months and 6 months. Unlike other studies that obtained a DF of ~3 cpm in the gastric remnant, Lee et al18 found that distal RSG patients had a lower DF value with an increased percentage of bradygastria (<2 cpm) irrespective of meal ingestion. Bracci et al28 observed the less common 3 cpm with an increased chance of bradygastria in children who underwent partial gastrectomy to augment bladder function.…”
Section: Discussionmentioning
confidence: 71%
“…Some changes in EGG parameters occur in the early days after subtotal gastrectomy 17. Lee et al18 enrolled subjects for distal robotic sleeve gastrectomy (RSG) who had undergone stomach surgery at least 1 year previously. Homma et al19 reported that a series of regular peaks of 3 cpm activity were not clearly visible in the EGGs running spectra recorded from patients who had undergone a distal gastrectomy with a short postoperative period (13~71 days in 13 subjects).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we do not yet know how stable this location is, what would make it potentially shift to another location nor do we know anything about potential variations between individuals. And we certainly do not know what happens to the pacemaker in pathophysiological conditions nor during gastric surgery . For example, in the gastric sleeve operation, the natural pacemaker is most probably removed, but we have no information if a subsidiary pacemaker would emerge, or anything about its location or rhythm.…”
Section: Future Researchmentioning
confidence: 99%
“…And we certainly do not know what happens to the pacemaker in pathophysiological conditions nor during gastric surgery. 35,36 For example, in the gastric sleeve operation, the natural pacemaker is most probably removed, but we have no information if a subsidiary pacemaker would emerge, or anything about its location or rhythm.…”
Section: Future Researchmentioning
confidence: 99%